Antidepressants and Risk of Type 2 Diabetes Mellitus: A Population-Based Nested Case-Control Study. Issue 4 (July 2020) - Kuo, Hsin-Ya; Chen, Hsiu-Min; Lee, Ching-Chih; Lee, Hsuan-Han; Kuo, Chuan-Jung; Hsu, Chun-Sheng; Pan, Chih-Chuan; Su, Ning; Chu, Che-Sheng
Abstract: Purpose/Background: The increased risk of type 2 diabetes mellitus (T2DM) among users of antidepressants (ADs) might be mediated by depression. We investigated whether ADs are associated with increased risk of T2DM in patients with depression. Moreover, the relationship between binding affinities of serotonin transporter (SERT) of ADs and the risk of T2DM is examined. Methods/Procedures: We conducted a retrospective nested case-control study using data from Taiwan's National Health Insurance Research Database between 2000 and 2013. A total of 3038 patients with depression, 1519 cases of T2DM, and 1519 controls matched for age, sex, and index date, were included. Exposure to ADs was categorized by type and SERT. The association between AD exposure and T2DM development was assessed using conditional logistic regression analysis. Findings/Results: No association between T2DM development and selective serotonin reuptake inhibitors (adjusted odds ratio [AOR], 1.01; 95% confidence interval [CI], 0.87–1.19; P = 0.962), serotonin-norepinephrine reuptake inhibitors (AOR, 1.13; 95% CI, 0.94–1.37; P = 1.196), tricyclic antidepressants (AOR, 1.01; 95% CI, 0.85–1.21; P = 0.906), or others (AOR, 0.88; 95% CI, 0.75–1.03; P = 0.104) was found. Alternatively, no association between individual ADs and potency of affinity to SERT and the risk of T2DM was found. Implications/Conclusions: No association between ADs and increase risk of T2DM was found in patients with depression. However, regular metabolic evaluations are recommended for patients with depression regularly taking ADs. Abstract : Supplemental digital content is available in the text.